Changes in Bench Press Velocity and Power After 8 Weeks of High-Load Cluster- or Traditional-Set Structures. Issue 10 (October 2020) - Davies, Timothy B.; Halaki, Mark; Orr, Rhonda; Helms, Eric R.; Hackett, Daniel A.
Abstract : Abstract: Davies, TB, Halaki, M, Orr, R, Helms, ER, and Hackett, DA. Changes in bench press velocity and power after 8 weeks of high-load cluster- or traditional-set structures. J Strength Cond Res 34(10): 2734–2742, 2020—This study investigated the effects of high-load cluster- vs. traditional-set structures using the bench press on velocity and power. Twenty-one resistance-trained individuals (male = 12, female = 9) performed a 3-week familiarization block followed by randomization into 1 of 2 upper- and lower-body split training routines performed for 8 weeks. The bench press was the only exercise manipulated with subjects using either cluster-set (CLUS, n = 11) or traditional-set (TRAD, n = 10) structures during training sessions. Subjects performed 4 sets of 5 repetitions at 85% 1 repetition maximum (1RM) with CLUS having a 30-second inter-repetition, and 3-minute interset rest while TRAD had a 5-minute interset rest. A load-velocity profile of relative loads derived from a 1RM test was used to assess velocity and power (absolute and relative to body mass) on the bench press. Significant improvements over time were found across various loads ranging from 45 to 75% 1RM for absolute and relative peak power ( p = 0.006–0.041), and mean power ( p = 0.001–0.032). Significant decreases over time were found at 55% 1RM and 65% 1RM for peak velocity ( p = 0.027 and p = 0.012, respectively) and mean velocity ( p = 0.047 and p = 0.022, respectively). There were no significant group or group by time interactions found for all outcomes. Within the context of high-load resistance training, set structure seems to be of less importance for changes in bench press velocity and power provided there is an intention to lift with maximal concentric velocity.